(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: In case of controlled cryogenic destruction of an epibulbar tumor, making direct temperature measurements in the tumor and surrounding tissues during the treatment process is difficult and dangerous. Infrared thermography (IRT) is, however, capable of imaging and recording only superficial-tissue temperature changes. Mathematical modeling can be used to assess the temperature distribution in the underlying structures based on their thermal physical characteristics. Purpose: To develop a model for temperature distribution in the ocular tunics in cryogenic destruction of conjunctival tumors located within a zone involving the ciliary body, in order to determine the tunic freezing parameters enabling reduced risk of complications while meeting the principles of ablastics. Materials and Methods: Twenty-five patients (25 eyes) underwent real-time IRT during controlled cryogenic destruction of benign and malignant epibulbar lesions located in the projection of the ciliary body onto the sclera. A model for temperature distribution in the ocular tunics in cryogenic destruction of conjunctival tumors located within a ciliary body zone was implemented using Microsoft Quick BASIC Version 4.5. Results: IRT-based analysis of temperature distribution found that, in cryogenic destruction of epibulbar tumors located in the projection of the ciliary body onto the sclera, initially, the sclera surrounding the centre of exposure gradually cooled down, while the cornea started cooling down rapidly only in 30 to 60 seconds, depending on tumor size and cryogenic unit parameters. The model (a) was developed while taking into account differences in heat conduction and heat capacity between the sclera, ciliary body and cornea, and (b) was also in agreement with the above finding. Conclusion: The method for IRT-based temperature field monitoring in cryogenic destruction of epibulbar tumors, and the thermal physical model developed will allow determining the individual cryogenic exposure parameters that would prevent excessive freezing of the surrounding structures (in particular, the ciliary body and corneal endothelium). IRT allows for the assessment of post-freezing increases in ocular tissue temperature to the baseline temperature, thus contributing to reduced complication rate, should a repeat cycle of cryogenic destruction of the tumor be required. Further studies should match individual cryogenic exposure durations computed by the model to the data relating to long-term clinical outcomes.